Calcium ion battery positive electrode active material, positive electrode material and preparation method and application thereof
By using vanadium-containing solid waste to prepare high-purity vanadium dioxide (VO2) as the positive electrode material of calcium ion battery, the problems of unstable structure and kinetic hysteresis of the positive electrode material of calcium ion battery are solved, and excellent cycle stability and rate performance are achieved.
Patent Information
- Application Number
- CN202411840081.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
AI Technical Summary
The existing calcium ion battery positive electrode materials have caused electrochemical reaction kinetic hysteresis and unstable electrode material structure due to Ca2+'s large ion radius and high charge density, which limits the development of calcium ion batteries.
By high-quality and resource utilization of vanadium-containing solid waste, high-purity vanadium dioxide (VO2) was prepared as the positive electrode active material for calcium ion batteries, and prepared by salt-free calcination method and solvent hydrothermal method.
The excellent cycle stability, superior rate performance and good reaction kinetics of the positive electrode material of calcium ion battery are achieved, and the problems of kinetic hysteresis and structural instability of electrochemical reactions are solved.
Smart Images

Figure CN119650675A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of calcium ion battery energy storage. The present invention is to prepare a positive electrode active material for a calcium ion battery from vanadium-containing solid waste, the preparation and characterization of the positive electrode material, and the research on the electrochemical performance. In particular, the present invention relates to a positive electrode active material for a calcium ion battery, a positive electrode material, and a preparation method and application thereof. Background Art
[0002] The extensive use of fossil energy will emit a large amount of carbon dioxide and other pollutants, causing serious pollution to the environment. In addition, fossil energy is a non-renewable energy with limited reserves. In recent years, renewable, sustainable development and low-carbon environmental protection have become very important in the energy world. At present, many countries are vigorously developing clean renewable energy, such as solar energy, wind energy, hydropower, geothermal energy and biomass energy. However, this type of energy usually depends on environmental factors such as geographical location, climate, season, etc., and is not directly usable. It is often necessary to convert it into electrical energy and store it through electrochemical energy storage devices, and then transmit it to where it is needed to achieve the utilization of clean energy.
[0003] In recent years, lithium-ion batteries have been widely used in electric vehicles and portable devices due to their long cycle life and high energy density. However, due to the uneven distribution and low content of lithium resources in the earth's crust, lithium-ion batteries are in short supply and their prices are unstable, which limits their further development. Among many new ion batteries, calcium-ion batteries are considered to be a promising electrochemical energy storage technology due to their strong competitiveness in cost, safety and energy density. However, due to the large ionic radius and high charge density of Ca2+, the electrochemical reaction kinetics are hysteretic and the electrode material structure is unstable. Therefore, it is urgent to propose a calcium-ion battery positive electrode active material with good electrochemical performance and excellent structural properties, a positive electrode material, and its preparation method and application. Summary of the invention
[0004] In order to solve the above-mentioned problems of the prior art, the present invention uses the vanadium-containing solid waste (i.e., vanadium-containing oxalate) generated in the alumina production process in a high-quality and resource-based manner to avoid harm to the natural environment and human health. A high-purity ammonium metavanadate (NH4VO3) sample is successfully recovered, and then a vanadium pentoxide (V2O5) sample is prepared by a salt-free roasting method, and then a VO2 sample is prepared by a solvent hydrothermal method, and finally the VO2 sample is used as a positive electrode active material for a calcium ion battery. While realizing the resource utilization of vanadium-containing solid waste and reducing the impact on the environment and human health, it also provides a low-cost, scalable positive electrode active material for the calcium ion battery system.
[0005] The technical solution adopted by the present invention is:
[0006] A positive electrode active material for a calcium ion battery, comprising vanadium dioxide, wherein an X-ray diffraction spectrum of the vanadium dioxide has diffraction peaks at diffraction angles of 25.24°, 14.34°, 29.98°, and 14.28°, an error of the X-ray diffraction angle 2θ of the vanadium dioxide is ±0.1°, and a main peak is at 25.24°;
[0007] A method for preparing the above-mentioned calcium ion battery positive electrode active material comprises the following steps:
[0008] S1: placing a container containing vanadium-containing solid waste in a 70° C. water bath, introducing a mixture of ammonia water and ammonia gas into the container and heating and stirring to maintain the ammonia concentration in the container at 30-60%;
[0009] S2: After the reaction in step S1 is completed, suction filtration is performed, and the obtained filtrate is placed in a container, the container is placed in a water bath for heating and stirring, and sulfuric acid is used to adjust the filtrate to a pH of 8-9;
[0010] S3: filtering the filtrate obtained in step S2, placing the filtrate in a container, placing the container in a water bath for heating and stirring, and adding hydrogen peroxide for reaction;
[0011] S4: After the reaction in step S3 is completed, take out the container and add ammonium sulfate, and then place it in a 70°C water bath for reaction;
[0012] S5: After the reaction in step S4 is completed, filtering is performed to obtain a filter residue, and drying is performed to obtain high-purity ammonium metavanadate;
[0013] S6: Place ammonium metavanadate in a crucible and heat the crucible until the color changes to a brick red sample;
[0014] S7: placing the brick red sample of step S6 into a muffle furnace for calcination, and after the calcination is completed, naturally cooling to room temperature to obtain a sample of vanadium pentoxide;
[0015] S8: placing vanadium pentoxide, sodium dodecyl sulfate and oxalic acid in another container, placing the container on a magnetic heating stirrer and stirring, and adding hydrogen peroxide dropwise to react to obtain a sample;
[0016] S9: pour the sample obtained in step S8 into a reaction kettle, cover the reaction kettle tightly and place it in an oven;
[0017] S10: After the reaction in step S9 is completed, the mixture is naturally cooled to room temperature, and then filtered after cooling. During the filtration, the mixture is first rinsed with deionized water for multiple times, and then rinsed with anhydrous alcohol for multiple times until there is no oily substance on the surface;
[0018] S11: putting the filter residue obtained by filtration into a dry container, and putting it into a vacuum oven for drying;
[0019] S12: Grinding the dried sample to obtain vanadium dioxide.
[0020] As a further description of the above scheme, in step S5, a self-made electrospun fabric is used for suction filtration;
[0021] In the step S1, ammonia water is added and ammonia gas is introduced at the same time to realize a mixed liquid, thereby obtaining high-concentration ammonia water, and the concentration of ammonia water is maintained at 30-60%.
[0022] A positive electrode material for a calcium ion battery comprises the positive electrode active material, a conductive agent and a binder, wherein the mass fraction of the positive electrode active material in the positive electrode material is 60-80%.
[0023] As a further description of the above solution, the mass fraction of the conductive agent in the positive electrode material is 5-30%, and the mass fraction of the binder in the positive electrode material is 5-20%.
[0024] As a further description of the above scheme, the conductive agent is conductive carbon black, carbon nanotubes, graphene, acetylene black or activated carbon; the binder is tetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, sodium hydroxymethyl cellulose or styrene-butadiene rubber.
[0025] A method for preparing the above positive electrode material comprises the following steps:
[0026] After the raw materials of the positive electrode active material, the conductive agent and the binder are mixed, a dispersant is added and mixed to form the positive electrode material.
[0027] A calcium ion battery electrode comprises the above-mentioned calcium ion battery positive electrode active material or the above-mentioned calcium ion battery positive electrode material.
[0028] A calcium ion battery comprises the above-mentioned calcium ion battery positive electrode active material or the above-mentioned calcium ion battery positive electrode material or the above-mentioned calcium ion battery electrode.
[0029] An application of the above-mentioned calcium ion battery positive electrode active material or the above-mentioned calcium ion battery positive electrode material or the above-mentioned calcium ion battery electrode or the above-mentioned calcium ion battery in the field of energy storage.
[0030] The beneficial effects of the present invention are:
[0031] The present invention uses a method of blending ammonia water and ammonia gas to make the ammonia water concentration required for the reaction reach 30-60%, which is higher than the concentration of commercially available ammonia water; in addition, electrostatic spinning homemade fabric is used to selectively filter the product ammonium metavanadate, thereby improving the yield and purity of the product; and vanadium dioxide is used as a positive electrode active material in calcium ion batteries, which can show excellent cycle stability, superior rate performance, good cycle reversibility, and good reaction kinetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art description are briefly introduced below.
[0033] Figure 1 is the XRD pattern of ammonium metavanadate product;
[0034] Figure 2 is the XRD pattern of vanadium pentoxide product;
[0035] Figure 3 is the XRD pattern of vanadium dioxide product;
[0036] Figure 4 The scanning electron microscope image of the vanadium dioxide product, the scale bars in the image are 0.5 μm, 250 nm, and the magnifications are 50,000 and 100,000 times;
[0037] Figure 5 The charge and discharge cycle performance curve of the obtained vanadium dioxide electrode;
[0038] Figure 6 The charge and discharge curve of the obtained vanadium dioxide electrode;
[0039] Figure 7 The rate performance curve of the obtained vanadium dioxide pole piece. DETAILED DESCRIPTION
[0040] The technical solution in this embodiment will be clearly and completely described below in conjunction with the accompanying drawings. The described embodiments are only some of the embodiments, not all of them. Based on the embodiments in this solution, all other embodiments obtained by ordinary technicians in this field without making creative work are within the protection scope of this solution.
[0041] Currently, existing calcium ion battery positive electrode materials still face the problems of low operating voltage, low energy density and insufficient cycle stability. The present invention provides a calcium ion battery positive electrode material with vanadium dioxide as an active substance, a preparation method and an application thereof.
[0042] A positive electrode active material for a calcium ion battery includes vanadium dioxide, wherein the X-ray diffraction spectrum of the vanadium dioxide has diffraction peaks at diffraction angles of 25.24°, 14.34°, 29.98°, and 14.28°, and the error of the X-ray diffraction angle 2θ of the vanadium dioxide is ±0.1°, wherein the main peak is at 25.24°. The vanadium dioxide of the present invention refers to VO2, which is a type of layered metal oxide. The characteristics of this type of material are that the layered structure provides open channels for the insertion and extraction of ions, large theoretical capacity, and suitable voltage platform. In addition, the valence state of the vanadium element ranges from positive trivalent to positive pentavalent, and the vanadium-based oxides accommodate many types, and the vanadium element reserves are abundant. Specifically, the length of vanadium dioxide is about 0.75μm and the width is about 62nm.
[0043] A method for preparing the above-mentioned calcium ion battery positive electrode active material comprises the following steps:
[0044] S1: Place a beaker containing vanadium-containing solid waste in a 70°C water bath, introduce a mixture of ammonia water and ammonia gas into the beaker and heat and stir to maintain the ammonia concentration in the beaker at 30-60%, and react for 5-6 hours;
[0045] S2: After the reaction in step S1 is completed, suction filtration is performed, and the obtained filtrate is placed in a beaker, the beaker is placed in a water bath for heating and stirring, and sulfuric acid is used to adjust the filtrate to a pH of 8-9;
[0046] S3: Filter the filtrate obtained in step S2, and put the filtrate into a beaker, put the beaker into a water bath for heating and stirring, and add hydrogen peroxide for reaction, and the reaction time is 30-60 minutes;
[0047] S4: After the reaction in step S3 is completed, take out the beaker and add ammonium sulfate, then put it in a 70°C water bath and react for 5-6 hours;
[0048] S5: After the reaction in step S4 is completed, filter to obtain a filter residue, and dry for 10-12 hours to obtain high-purity ammonium metavanadate;
[0049] S6: Place ammonium metavanadate in a crucible and heat the crucible on a magnetic heating stirrer. Stirring is not required. Use a glass rod to stir the sample in the crucible until the color changes to brick red.
[0050] S7: Put the crucible containing the brick red sample into a muffle furnace, calcine at 350°C for 10-12h, cool naturally for more than 12h after calcination, and take out the sample, which is vanadium pentoxide; specifically, the vanadium pentoxide of the present invention refers to V2O5, and "ammonium metavanadate" refers to NH4VO3.
[0051] S8: Put vanadium pentoxide, sodium dodecyl sulfate and oxalic acid in a small beaker, place it on a magnetic heating stirrer and stir, add hydrogen peroxide dropwise, and react for 1-3 hours;
[0052] S9: Pour the sample in the beaker into the reactor, cover the reactor tightly and place it in an oven at 180°C for 22-24 hours;
[0053] S10: After the reaction in step S9 is completed, the mixture is naturally cooled for 12 hours, and then filtered. During the filtration, the mixture is first rinsed with deionized water for several times, and then rinsed with anhydrous alcohol for several times until there is no oily substance on the surface;
[0054] S11: The filtrate residue obtained by filtration is placed in a dry beaker, and then placed in a vacuum oven at 80° C. and dried for 10-12 hours;
[0055] S12: Grind the dried sample to obtain vanadium dioxide. In the production process of alumina industry, a large amount of vanadium-containing solid waste (i.e., vanadium-containing oxalates) will be generated. If these vanadium-containing oxalates are randomly piled up or discarded, they will not only occupy a large amount of land resources, but also cause serious harm to the natural environment and human health. Therefore, the high-quality and resource-based utilization of vanadium-containing oxalates, and then the salt-free roasting method and solvent hydrothermal method are used to obtain high-purity layered vanadium oxides, and then the salt-free roasting method is used as a raw material to prepare vanadium dioxide (VO2) as a positive electrode active material for calcium ion batteries, which can not only solve environmental problems, but also create considerable economic and social benefits. Based on the above considerations, the present invention utilizes vanadium-containing solid waste (i.e., vanadium-containing oxalate) in a high-quality and resource-based manner, and provides a positive electrode active material with excellent electrochemical properties and good reaction kinetics for calcium ion batteries, which can solve the environmental pollution problem while creating considerable economic benefits; the present invention provides the use of VO2 as a positive electrode active material for calcium ion batteries, which is subjected to electrochemical testing to obtain excellent cycle stability, superior rate performance, fast reaction kinetics, and good cycle reversibility.
[0056] In step S5 of the present invention, a self-made electrospun fabric is used for filtration. The advantage of this design is that the electrospun fabric is electrospun according to the size of the product, and the ammonium metavanadate product is selectively filtered out, thereby improving the yield and purity of the product.
[0057] In step S1 of the present invention, ammonia water is added and ammonia gas is introduced at the same time to realize a mixed liquid, thereby obtaining high-concentration ammonia water. The concentration of ammonia water is maintained at 30-60%, which is higher than the concentration of commercially available ammonia water of 25-28%.
[0058] A positive electrode material for a calcium ion battery comprises the positive electrode active material, a conductive agent and a binder, wherein the mass fraction of the positive electrode active material in the positive electrode material is 60-80%.
[0059] The mass fraction of the conductive agent in the present invention accounts for 5-30% of the positive electrode material, and the mass fraction of the binder in the positive electrode material accounts for 5-20%.
[0060] The conductive agent of the invention is conductive carbon black, carbon nanotube, graphene, acetylene black or activated carbon; wherein the binder is tetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, sodium hydroxymethyl cellulose or styrene-butadiene rubber.
[0061] A method for preparing the above positive electrode material comprises the following steps:
[0062] After mixing the raw materials of the positive electrode active material, the conductive agent and the binder, a dispersant is added and mixed to form a positive electrode material, wherein the dispersant is selected from water, ethanol, N-methylpyrrolidone, methanol, propanol or isopropanol.
[0063] A calcium ion battery electrode comprises the above-mentioned calcium ion battery positive electrode active material or the above-mentioned calcium ion battery positive electrode material.
[0064] The method for preparing a calcium ion battery electrode of the present invention comprises the following steps:
[0065] After mixing raw materials including positive electrode active materials, conductive agents and binders, a dispersant is added, and the resulting product is coated on a conductive current collector, and after drying, a calcium ion battery electrode is obtained, wherein the conductive current collector is selected from carbon cloth, carbon paper, carbon felt, titanium foil, stainless steel foil, copper foil, aluminum foil, foamed nickel or foamed copper.
[0066] A calcium ion battery comprises the above-mentioned calcium ion battery positive electrode active material or the above-mentioned calcium ion battery positive electrode material or the above-mentioned calcium ion battery electrode. The calcium ion battery of the present invention refers to a battery that relies on the movement of calcium ions between the positive and negative electrodes. The calcium ions may exist in the active material of the positive or negative electrode of the battery, or in the electrolyte.
[0067] An application of the above-mentioned calcium ion battery positive electrode active material or the above-mentioned calcium ion battery positive electrode material or the above-mentioned calcium ion battery electrode or the above-mentioned calcium ion battery in the field of energy storage.
[0068] Example 1
[0069] In the above-mentioned positive electrode active material, vanadium dioxide is prepared by the following steps:
[0070] Step (1) Take 100 g of vanadium-containing solid waste in a dry 500 mL beaker and place it in an 80° C. drying oven for 8-10 hours. If conditions permit, cover the beaker with plastic wrap and poke some small holes;
[0071] Step (2) The following steps are all carried out in a fume hood;
[0072] Step (3) The temperature of the heat-collecting constant temperature magnetic stirrer (water bath) is set to 70° C. and the stirring rate is 270-320 rpm. The water bath in the following steps is set to this condition.
[0073] Step (4) Weigh 20-40 g of the dried vanadium-containing solid waste sample obtained in step (1) into a 500 mL dry beaker and place it in a 30×7 mm rotor (type B);
[0074] Step (5) placing the beaker in step (4) in a 70° C. water bath and setting up the instrument;
[0075] Step (6) introducing a mixed solution of ammonia gas and ammonia water into the beaker of step (5) to maintain the concentration of ammonia water in the beaker at 30-60%, and sealing the beaker with plastic wrap, and the reaction time is 5-6 hours;
[0076] Step (7) Take out the beaker after the reaction in step (6), filter the obtained brown-yellow solid-liquid mixture, put the obtained filtrate into a 500 mL dry beaker, then put in a rotor, and put the beaker into a 70° C. water bath;
[0077] Step (8) Add 98% concentrated sulfuric acid by mass to the beaker placed in the water bath in step (7) until the pH of the solution is 8-9, and add dropwise using a disposable dropper at a rate of 6-12 mL / h. The amount of concentrated sulfuric acid added is 6-12 mL. After adding 1 mL of concentrated sulfuric acid, it takes 1-2 minutes to wait before the next addition.
[0078] Step (9) In step (8), pH test paper is used to measure pH in the early stage. When the solution is close to pH = 9, a pH meter is used to measure the solution pH = 8-9;
[0079] Step (10) Filter the solution in the beaker obtained in step (9) by suction, and put the filtrate into a 500 mL dry beaker, then put a rotor in it, and put the beaker into a 70° C. water bath;
[0080] Step (11) Wait for 3-4 minutes, use this time to weigh 15-30 mL of 30% hydrogen peroxide, and use a 50 mL measuring cylinder to weigh;
[0081] Step (12) adding the hydrogen peroxide weighed in step (11) dropwise into the beaker in step (10) at a dropping speed of 60-120 mL / h and covering with plastic wrap, and the reaction time is 30-60 min;
[0082] Step (13) Using the reaction time of step (12), weigh 20-40 g of ammonium sulfate using an analytical balance;
[0083] Step (14) After the reaction time of step (12) is completed, the beaker in the water bath is taken out, and the weighed ammonium sulfate is poured into the beaker at once, and then covered with plastic wrap;
[0084] Step (15) The beaker obtained in step (14) is placed in a water bath again, and the reaction time is 5-6 hours;
[0085] Step (16) After the reaction in step (15) is completed, the liquid in the beaker is filtered using a homemade electrospinning fabric, and the liquid is rinsed with deionized water multiple times during the filtration process;
[0086] Step (17) putting the filter residue obtained in step (16) together with the fabric into a dry beaker, placing a round filter paper on the filter residue, and then sealing the beaker with plastic wrap;
[0087] Step (18) Place the beaker of step (17) in an oven at 80°C and dry for 10-12 hours;
[0088] Step (19) The filter residue in step (18) is taken out, cooled to room temperature and lightly ground to obtain a light yellow solid NH4VO3;
[0089] Step (20) The light yellow solid in step (19) is spread flat in a corundum square crucible, and the crucible is placed on a magnetic heating stirrer for heating without stirring;
[0090] Step (21) in step (20), the sample in the crucible is moved with a glass rod until the color changes to brick red;
[0091] Step (22) placing the crucible containing the brick red sample in step (21) into a muffle furnace, calcining at 350° C. for 10-12 h, and naturally cooling for more than 12 h after calcination to take out the sample, which is V2O5;
[0092] Step (23) Weigh 0.2-0.5 g of the V2O5 in step (22), and then weigh 0.5-1 g of sodium dodecyl sulfate and 0.3-0.5 g of oxalic acid, and put the three into a dry small beaker;
[0093] Step (24) Add 20 mL of deionized water to the small beaker in step (23), place an A-type rotor (15×7 mm), and then place the small beaker on a magnetic heating stirrer for stirring. The stirring speed is set to 290-340 rpm, and no heating is required;
[0094] Step (25) adding 10 mL of 9% hydrogen peroxide dropwise to step (24) at a rate of 60-120 mL / h;
[0095] Step (26) After step (25) is added dropwise, the beaker is sealed with plastic wrap and reacted for 1-3 hours;
[0096] Step (27) After the reaction in step (26), pour the sample in the beaker into the reaction kettle, cover the reaction kettle tightly and place it in an oven at 180°C for 22-24 hours;
[0097] Step (28) Step (27) After the reaction, the mixture was naturally cooled for 12 hours, and then filtered after cooling. During the filtration, the mixture was first rinsed with deionized water for several times, and then rinsed with anhydrous alcohol for several times until there was no oily substance on the surface;
[0098] Step (29) placing the filter residue obtained by suction filtration in step (28) into a dry beaker, sealing the beaker with plastic wrap, and placing it in a vacuum oven at 80° C. for drying for 10-12 hours;
[0099] Step (30) grinds the dried filter residue to obtain positive electrode active material VO2.
[0100] The preparation process of the calcium ion positive electrode material and the calcium ion battery of the present invention is as follows:
[0101] First, vanadium dioxide is synthesized: ammonia water is added to vanadium-containing solid waste, heated and stirred, and filtered to obtain a filtrate; concentrated sulfuric acid is added to the filtrate to adjust the pH value (pH=8-9), and filtered again to obtain a filtrate; hydrogen peroxide is added to the filtrate; ammonium sulfate is then added to the solution, and filtered to obtain a filter residue after reaction; the filter residue is dried to obtain ammonium metavanadate, where "ammonium metavanadate" refers to NH4VO3; the ammonium metavanadate is calcined to obtain vanadium pentoxide; and vanadium pentoxide is hydrothermally reacted with sodium dodecyl sulfate and oxalic acid to obtain vanadium dioxide.
[0102] Then, the active material (vanadium dioxide), the conductive agent (including amorphous carbon material and / or graphitized carbon material) and the binder (including polymer materials such as polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, etc.) are mixed in a certain proportion (the mass ratio of the three in the mixture can be active material: 60-80%, conductive agent: 5-30%, binder: 5-20%), and a dispersant (which can be water, ethanol or N-methylpyrrolidone) is added to form a paint-like slurry;
[0103] Then, the electrode sheet is made. The obtained slurry can be applied on a conductive current collector (including carbon paper, carbon cloth, carbon felt, titanium foil, stainless steel foil, copper foil, aluminum foil, foam nickel, foam copper) by, but not limited to, spin coating, blade coating, spray coating, or dip coating. After coating and drying, an electrode sheet is obtained. The electrode loading can be 1-4 mg / cm2.
[0104] Finally, the obtained electrode sheet is used to assemble a calcium ion battery (including an aqueous solution system and an organic system) as the positive electrode of the calcium ion battery.
[0105] The calcium ion battery positive electrode material of the present invention is further illustrated by specific examples below.
[0106] In the following examples, the information of the instruments used is:
[0107] X-ray diffractometer: Manufacturer: Rigaku, Japan, Model: Miniflex600.
[0108] Scanning electron microscope: Manufacturer: Hitachi, Japan, model: HitachiSU8010.
[0109] Electrochemical workstation: Manufacturer: Shanghai Chenhua Instrument Co., Ltd., Model: CHI660E.
[0110] Blue Electric test system: Manufacturer: Wuhan Blue Electric Electronics Co., Ltd., Model: CT2001A.
[0111] In the following examples, the information of the reagents used is shown in the following table:
[0112]
[0113] Other reagents were of analytical grade and battery grade and were purchased from Sinopharm Reagents.
[0114] The above VO2 solid was analyzed by X-ray diffractometer to obtain the XRD curve of VO2 solid, as shown in Figure 1 As shown in the figure, "PDF 01-081-2392" refers to the VO2 standard spectrum, and the sample obtained in this embodiment matches the standard PDF card 01-081-2392 very well.
[0115] Figure 2 As shown, vanadium pentoxide (V2O5) is obtained by calcining ammonium metavanadate (NH4VO3). It is analyzed by X-ray diffractometer, and the obtained XRD curve matches well with the standard pdf card.
[0116] like Figure 3 As shown, in the spectrum of vanadium dioxide obtained in this example, the positions of characteristic peaks are 25.24°, 14.34°, 29.98°, and 14.28°, with the main peak at 25.24°, the second strongest peak at 14.34°, and the third strongest peak at 29.98°.
[0117] like Figure 4 As shown, the vanadium dioxide solid was detected by electron scanning microscopy to obtain a SEM image. The length of the obtained sample was about 0.75 μm, the width was about 62 nm, and the sample showed an irregular strip morphology.
[0118] The vanadium dioxide sample obtained in this example was made into an electrode sheet and subjected to electrochemical testing in the following steps:
[0119] Using 0.3 mL NMP as a dispersant, 0.06 g of vanadium dioxide solid, 0.03 g of acetylene black, and 0.01 g of polyvinylidene fluoride were mixed evenly, coated on a carbon cloth material, and vacuum dried at 105 ° C to obtain a vanadium dioxide electrode sheet;
[0120] The vanadium dioxide electrode sheet is used as the working electrode, a platinum sheet is used as the auxiliary electrode, a saturated silver chloride electrode is used as the reference electrode, and a 1 mol / L calcium nitrate aqueous solution is used as the electrolyte to perform an electrochemical test on the vanadium dioxide electrode sheet;
[0121] The electrode sheet obtained in this embodiment is used to perform a charge-discharge cycle performance test to obtain a charge-discharge cycle performance curve, such as Figure 5 As shown, at a current density of 5 A / g, after 1000 cycles, the discharge specific capacity is 88.3 mAh / g, showing excellent cycle stability. In addition, its coulombic efficiency exceeds 98%, which also proves that vanadium dioxide has high electrochemical reversibility.
[0122] The electrode sheet obtained in this example was subjected to charge and discharge tests to obtain charge and discharge curves of different numbers of cycles at a current density of 5A / g, as shown in FIG. Figure 6 After multiple charges and discharges, the charge and discharge voltage difference of the electrode is low, indicating that the insertion and extraction of calcium ions do not have a significant effect on the working voltage of the electrode, indicating that the electrode material has good stability.
[0123] The electrode sheet obtained in this embodiment was used to perform rate performance test. Figure 7 As shown in the figure, at current densities of 1, 2, 3, 4, and 5 A / g, the discharge capacity of vanadium dioxide is 85.9 mAh / g, respectively. When the current density gradually increases, the battery capacity decays slowly, indicating that the material is relatively stable. In addition, when the current density is restored to 1 A / g, the specific capacity of vanadium dioxide can be restored to 81.1 mAh / g, which is very close to the capacity at the initial current density of 1 A / g, indicating that the vanadium dioxide sample has excellent rate performance and fast charge and discharge capabilities.
[0124] The above is only an embodiment of the present application and does not constitute any form of limitation to the present application. Although the present application is disclosed as above with a preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A calcium ion battery positive electrode active material, characterized in that: The invention comprises vanadium dioxide, wherein the X-ray diffraction spectrum of the vanadium dioxide has diffraction peaks at diffraction angles of 25.24°, 14.34°, 29.98° and 14.28°, the error of the X-ray diffraction angle 2θ of the vanadium dioxide is ±0.1°, and the main peak is at 25.24°.
2. A method for preparing a positive electrode active material for a calcium ion battery according to claim 1, characterized in that: The following steps are involved: S1: placing a container containing vanadium-containing solid waste in a 70° C. water bath, introducing a mixture of ammonia water and ammonia gas into the container and heating and stirring to maintain the ammonia concentration in the container at 30-60%; S2: After the reaction in step S1 is completed, suction filtration is performed, and the obtained filtrate is placed in a container, the container is placed in a water bath for heating and stirring, and sulfuric acid is used to adjust the filtrate to a pH of 8-9; S3: filtering the filtrate obtained in step S2, placing the filtrate in a container, placing the container in a water bath for heating and stirring, and adding hydrogen peroxide for reaction; S4: After the reaction in step S3 is completed, take out the container and add ammonium sulfate, and then place it in a 70°C water bath for reaction; S5: After the reaction in step S4 is completed, filtering is performed to obtain a filter residue, and drying is performed to obtain high-purity ammonium metavanadate; S6: Place ammonium metavanadate in a crucible and heat the crucible until the color changes to a brick red sample; S7: placing the brick red sample of step S6 into a muffle furnace for calcination, and after the calcination is completed, naturally cooling to room temperature to obtain a sample of vanadium pentoxide; S8: placing vanadium pentoxide, sodium dodecyl sulfate and oxalic acid in another container, placing the container on a magnetic heating stirrer and stirring, and adding hydrogen peroxide dropwise to react to obtain a sample; S9: pour the sample obtained in step S8 into a reaction kettle, cover the reaction kettle tightly and place it in an oven; S10: After the reaction in step S9 is completed, the mixture is naturally cooled to room temperature, and then filtered after cooling. During the filtration, the mixture is first rinsed with deionized water for multiple times, and then rinsed with anhydrous alcohol for multiple times until there is no oily substance on the surface; S11: putting the filter residue obtained by filtration into a dry container, and putting it into a vacuum oven for drying; S12: Grinding the dried sample to obtain vanadium dioxide.
3. The method for preparing a positive electrode active material for a calcium ion battery according to claim 2, characterized in that: In the step S5, a self-made electrospun fabric is used for suction filtration. In the step S1, ammonia water is added and ammonia gas is introduced at the same time to realize a mixed liquid, thereby obtaining high-concentration ammonia water, and the concentration of ammonia water is maintained at 30-60%.
4. A calcium ion battery positive electrode material, characterized in that: The positive electrode active material according to claim 1 is included, and the mass fraction of the positive electrode active material in the positive electrode material is 60-80%.
5. The calcium ion battery positive electrode material according to claim 4, characterized in that: The mass fraction of the conductive agent in the positive electrode material is 5-30%, and the mass fraction of the binder in the positive electrode material is 5-20%.
6. The positive electrode material according to any one of claims 4 to 5, characterized in that: The conductive agent is conductive carbon black, carbon nanotubes, graphene, acetylene black or activated carbon; the binder is tetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, sodium hydroxymethyl cellulose or styrene-butadiene rubber.
7. A method for preparing a positive electrode material for a calcium ion battery according to any one of claims 4 to 6, characterized in that: The steps include: After the raw materials of the positive electrode active material, the conductive agent and the binder are mixed, a dispersant is added and mixed to form the positive electrode material.
8. A calcium ion battery electrode, characterized in that: It comprises the calcium ion battery positive electrode active material according to claim 1 or the calcium ion battery positive electrode material according to any one of claims 4-6.
9. A calcium ion battery, characterized in that: It comprises the calcium ion battery positive electrode active material according to claim 1 or the calcium ion battery positive electrode material according to any one of claims 4 to 6 or the calcium ion battery electrode according to claim 8.
10. Use of the calcium ion battery positive electrode active material according to claim 1, the calcium ion battery positive electrode material according to any one of claims 4 to 6, the calcium ion battery electrode according to claim 8, or the calcium ion battery according to claim 9 in the field of energy storage.